Produtividade de duas cultivares de cafeeiro utilizando-se sistema de irrigação localizada por gotejamento na região noroeste do estado do Paraná - Costa, André Ribeiro da (2010)
The techniques of irrigation, permits the introduction of the agricultural cultures in areas, that even are considered as unsuited to crop, because of the incident of climactic adversity. Besides, in the case of coffee culture contributes for the increase of productivity,and of the improvement of the quality of drink, even same in traditionally producer of grains, as the Northwest and North Regions of Parana State. Search - if in the irrigation the regularity in the water supply necessary for the plants. It is possible to take place the application of the fertilizers,through of the irrigation water, being this techinique called fertirrigation. Thus, the fertilizers are applied, with more efficiency and with the use of smaller labor, therefore leading a reduction in the production costs, what favors the increase of the gain of coffee - growth and the realization of new investments in the tillings. Inside this context presented, this work has for objective to value the effect of cultivations (non irrigated, irrigated and fertirrigated) combined with percentages of doses of NPK (50%, 100%, 150%, 200%) in the productivity and in the number of plagiotropic branches, in the coffee cultivars IAPAR - 59 and Obatã. The experiment was conducted in a experimental area of the Technical Center of Irrigation (CTI), bound institution to Department of Agronomy (DAG) of the State University of Maringá (UEM). The observation of the results, permits infer what were detected significant differences, in the two analyzed variables. The irrigation and fertirrigation, promoted increases in the productivity and in the number of plagiotropic total branches of the coffee plants, in study. In respect to first variable been found an answer common, in other words, the dose more appropriate of NPK for both cultivars in the various cultivations been the of 150% that corresponded the application of 225 kg ha-1 of N, 45 kg ha-1 of P2O5 and 225 kg ha-1 of K2O and in relation to second variable can to claim to be what been not found an uniform behaviour, that is were found different answers, concerning doses of NPK in the different cultivations for each grow coffee, studied.